2021
DOI: 10.1007/s00267-021-01533-3
|View full text |Cite
|
Sign up to set email alerts
|

An Impact Assessment of Beach Wrack and Litter on Beach Ecosystem Services to Support Coastal Management at the Baltic Sea

Abstract: As accumulation zones, sandy beaches are temporal sinks for beach wrack and litter, both often seen as nuisances to tourists. Consequently, there is a need for beach management and an enhanced political interest to evaluate their ecosystem services. We applied a new online multidisciplinary assessment approach differentiating between the provision, potential, and flow at German and Lithuanian beaches (Southern Baltic Sea). We selected a set of services and assessed four beach scenarios developed accordingly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Several studies have already shown that ecosystem service assessments can support stakeholder communication and policy implementation [29,30]. In our case, it can serve as a tool to visualize potential benefits and trade-offs and analyze patterns and processes at a regional level [25,42,48].…”
Section: Expert-and Stakeholder-based Esa Approachmentioning
confidence: 85%
See 1 more Smart Citation
“…Several studies have already shown that ecosystem service assessments can support stakeholder communication and policy implementation [29,30]. In our case, it can serve as a tool to visualize potential benefits and trade-offs and analyze patterns and processes at a regional level [25,42,48].…”
Section: Expert-and Stakeholder-based Esa Approachmentioning
confidence: 85%
“…While former studies gave first insights into the potential usage of ESA for the implementation of water quality improvement measures and their use within the integrated coastal management processes [25,39,48], they lacked concrete information about the application within the WFD implementation cycle itself. Based on our results and the experience we created, we see the following possible applications of ESA and PM in the selection and implementation of possible measures as exemplary for the German WFD implementation cycle (Figure 5).…”
Section: Implementation Of Different Assessment Approaches Into the Wfdmentioning
confidence: 99%
“…The scale ranged from not important (1) to very important (5). Further, in this study, these values were transformed to 0, 1, 2, 4 and 8, respectively, and analyzed using the methodology presented in Robbe et al [30]. This non-linear transformation of the scores allowed the highlighting of the highest scoring value, thus having more robust and clear mapping results and a better understanding of the most important and valuable ES.…”
Section: Relative Importance (Ri) Of Ecosystem Servicesmentioning
confidence: 99%
“…Results based on the flexible 0-5 ranking system and the linkage to geobiophysical spatial units (e.g., land cover, biotope, vegetation or soil types) in ES maps not only provide wide application ranges for decision-making, but also ensure that none of the ES are overlooked [26,27]. A more recent attempt to develop the matrix approach focused on ranking or assigning weights for ES categories [28][29][30], demonstrating that perceptions and priorities of well-being are area-and society-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive human activities have a significant impact on the relationships between ecosystem services [4,5] and overlooking ES trade-offs and synergies may lead to a reduction in the provisioning abilities of certain ESs and may even threaten ecosystem stability [6,7]. Identifying trade-offs and synergies between ESs and clarifying their spatiotemporal variations and driving factors are crucial for optimizing multiple services and avoiding damaging other services while improving a particular service [8,9]. It is of great significance to promote ESs from theoretical research to management practice.…”
Section: Introductionmentioning
confidence: 99%